The effect of emotional intelligence and communication skills on critical reasoning dimensions in realizing the profile of Pancasila students - Anggrarina; Dini Rakhmawati; Iin Purnamasari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to test and analyze (1) the effect of emotional intelligence on critical reasoning dimensions, (2) the effect of communication skills on critical reasoning dimensions, and (3) the effect of emotional intelligence and communication skills simultaneously on critical reasoning dimensions. The population and sample consisted of/involved 31 people. The instrument tests used were validity and reliability tests. The classical assumption test used the normality, linearity, multicollinearity, and heteroscedasticity tests. Data analysis uses multiple linear regression tests, F tests (ANOVA), and t-tests. Based on the research results, it can be concluded that (1) Emotional intelligence positively and significantly influences the critical reasoning dimension. It is based on the results of a positive t-test, proven by the calculated t1 result of 21.393> t table 2.0423, (2) Communication skills have a positive and significant effect on the critical reasoning dimension. This is based on a positive t-test, proven by the calculated t2 result of 6.840> t table 2.0423, (3) The effect of emotional intelligence and communication skills simultaneously positively and significantly affects the critical reasoning dimension. This is based on the results of a positive F-test, proven by the calculated F value> F table (369.315> 3.34)